PENINGKATAN KOMPETENSI PEMBUATAN DAN VISUALISASI DATA BAGI TENAGA KEPENDIDIKAN - Ihwan Rahman Bahtiar; Muhammad Ashar Nur; Ahmad Marzuq (Universitas Majalengka, 2022)
Current technological developments encourage digital transformation in various fields. The work system and public services that were originally held manually are now turning into all-digital ones. Entering this era of digital transformation, data has become a valuable asset for an institution. Therefore, human resources are needed who are able to collect data, process, and present it quickly and attractively at this time. Jakarta State University (UNJ), as one of the largest campuses in Indonesia, is faced with the problem of the uneven ability of its educational staff in digitizing data and processing it. This problem arises because of the lack of training provided to educate staff to improve technology and information literacy. Through this service activity, the team intends to improve the competence of the staff within UNJ in creating and visualizing data using the Google platform. The blended workshop implementation method is a workshop that is carried out by combining synchronous and asynchronous activities. Synchronous activities are carried out through the Zoom Cloud Meeting platform, while asynchronous activities are carried out using the Microsoft Teams platform. The activity which was carried out for 16 hours of training was able to improve the ability of the tending in terms of processing and visualizing data. This can be seen from the results of the workshops that were collected in the form of visualization of data related to their respective work units which can be updated and viewed in real-time or direct.